On the Failure (Success) of the Markets for Longevity Risk Transfer. (15th March 2017) - MacMinn, Richard; Brockett, Patrick
ABSTRACT : Longevity risk is the chance that people will live longer than expected. That potential increase in life expectancy exposes insurers and pension funds to the risk of not having sufficient funds to pay a longer stream of annuity benefits than promised. Longevity bonds and forwards provide insurers and pension funds with financial market instruments designed to hedge the longevity risk that these organization face. The European Investment Bank and World Bank have both discussed longevity bond issues, but those issues have failed due to insufficient demand. Forward contracts have also been created, but that market remains dormant. The extant literature suggests that these failures may be due to design or pricing problems. In this article the analysis shows that the market failure is instead due to a moral hazard problem.